Spectroscopic and elementary characterization of humic substances in organic substrates - da Silva, Rubens Ribeiro; Lucena, Guilherme Nunes; Machado, Ângela Franciely; de Freitas, Gilson Araújo; Matos, Antônio Teixeira; Abrahão, Walter Antônio Pereira (Comunicata Scientiae, 2018)
The humic substances, major constituents of the organic matter of the substrates, play an important role in plant development, including: the availability of nutrients, the generation of negative charges (CEC) and the buffering effect. Based on this, this study aimed to use the molecular absorption spectroscopy in the ultraviolet-visible region (UV-VIS), the vibrational spectroscopy Fourier transform infrared (FTIR) and the elementary analysis CHN/O techniques to characterize the humic acid (HA) and fulvic acid (FA) fractions of the humic substances of five organic substrates, named as T1, T2, T3, T4, and T5, which were produced at the Federal University of Tocantins – Campus Gurupi. The molecular absorption spectra in UV-VIS and FTIR on the T1, T2, T3, T4 and T5 substrates showed humification, the formation of negative charges, which is related to the cation exchange capacity (CEC) and the complexation of metal ions that are considered nutrients. The biggest humification was shown for the T4 substrate, in function of its higher cabon-acid humic/carbon-acid fulvic ratio and the lower C/N ratio, allied to a negative charge generation, the low E4/E6 ratio found in the humic acid fraction. The complexation of metal nutrient ions indicates the greatest potencial of its use for seedlings production and the conservation of the chemical and physical properties of the organic substrate.